(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
A Dravya (drug) can perform its action due to its Gunas (properties). Gunas act as a medium for predicting or assessing Karma (drug action). Understanding Guna will play a leading role in the application of Dravyas in treatment. According to Acharya Sushruta, Ushna guna is having a prominent action on Pachana (digestion). This concept was utilized to assess the action of Ushna and Sheeta guna on Agni by the application of an in vitro digestion model. A standardized static in vitro digestion (INFOGEST) method was followed for three groups (i) Mudga alone (S) (ii) Mudga with Ushna drug (Maricha - Piper nigrum Linn.) (SM) and (iii) with Sheeta drug (Usheera -Vetiveria zizanoides Linn.) (SU), separately. The concentration of carbohydrates and proteins in different stages of digestion was estimated and bio-accessibility in each group was calculated and compared. Both the test groups showed significant effects on the bio-accessibility of Carbohydrates of Mudga. The test drugs do not have any effect on protein digestion in Mudga. But at the intestinal phase at 60 min, a significant difference was noted between the trial groups at p=0.0391. Ushna guna of Maricha and Sheeta guna of Usheera showed their effects on the carbohydrate bio-accessibility of Mudga during in vitro static digestion. The effect was more pronounced in the Maricha group. Maricha being an Ushna dravya must have modulated the enzymatic activity in a better way and improved the bio-accessibility of CH in Mudga as found in this study.